Effects of low concentrations of glyphosate-based herbicide factor 540® on an agricultural stream freshwater phytoplankton community. (February 2018) - Smedbol, Élise; Gomes, Marcelo Pedrosa; Paquet, Serge; Labrecque, Michel; Lepage, Laurent; Lucotte, Marc; Juneau, Philippe
Abstract: Residual glyphosate from glyphosate based herbicides (GBH) are ubiquitously detected in streams draining agricultural fields, and may affect phytoplankton communities present in these ecosystems. Here, the effects of the exposure (96 h) of a phytoplankton community collected in an agricultural stream to various glyphosate concentrations (1, 5, 10, 50, 100, 500 and 1000 μg l −1 ) of Factor 540 ® GBH were investigated. The lowest GBH concentration of 1 μg l −1 reduced chlorophyll a and carotenoid contents. Low glyphosate concentrations, such as 5 and 10 μg l −1, promoted changes in the community's structure and reduced the diversity of the main algal species. At glyphosate concentrations ranging from 50 to 1000 μg l −1, the phytoplankton community's composition was modified and new main species appeared. The highest glyphosate concentrations (500 and 1000 μg l −1 ) affected the shikimate content, the lipid peroxidation and the activity of antioxidant enzymes (superoxide dismutase, catalase and ascorbate peroxidase). These results indicate that GBH can modify structural and functional properties of freshwater phytoplankton communities living in streams located in agricultural areas at glyphosate concentrations much inferior to the 800 μg l −1 threshold set by the Canadian guidelines for the protection of aquatic life. Highlights: GBH can modify the structure and functions of phytoplankton communities. Physiological impacts occur at concentrations much lower than the Canadian standard. Shikimate content can be used as an indicator of GBH exposure in phytoplankton.